Participatory epidemiological approaches for risk assessment of bed bug (Insecta: Hemiptera: Cimicidae) infestation in public hospitals in the city of Faisalabad, Punjab, Pakistan - Arzoo Ashraf; Muhammad Sohail Sajid; Hafiz Muhammad Rizwan; Kashif Hussain; Muhammad Asif Mahmood; Muhammad Imran Arshad; Zain ul Abdin; Shumaila Ashraf; Malcolm K. Jones; Dalia Fouad; Farid S. Ataya (BMC Public Health)
Abstract This study was to determine risk assessment associated with bed bugs (Insecta: Hemiptera: Cimicidae) using participatory epidemiological tools in the selected public hospitals of district Faisalabad, Punjab, Pakistan. Bed bugs were collected and morphologically identified through a standard taxonomic key. A descriptive cross-sectional survey of patients using a pre-designed questionnaire containing open-ended and closed-ended questions was conducted for six months between January 2023 and June 2023. Of the 384 participants, 113 (29.43%) had experienced itching or skin irritation presumably from the bed bug feeding activity. The study further revealed patients above age 40 (35.43%) and males (30.57%) experienced greater skin irritation responses compared to other participants. Among administrative divisions (tehsils) in the city of Faisalabad, Tehsil Sadar had the highest number of participants with itching or skin irritation (35.48%), while Tehsil Chak Jhumra had the lowest number (24.62%). Most observations of bed bugs by patients were in their beds (10.42%), with chairs (3.91%) being the second most reported location. However, we found bed bugs from only 17 (4.42%) beds and 5 (1.30%) from chairs. A majority of patients (60.9%) reported daily change of bedding; however, a significant proportion (29.9%) reported infrequent changes. About 25.5% of the patients shared beds with others and about 77.1% of patients brought their own bedding or clothing to the hospitals. The current study concluded that the bed bug infestation is a problem in the public hospitals of Faisalabad, Punjab, Pakistan. Risk factors such as sharing a bed, infrequent change of bedding, and bringing personal bedding to hospital while having medical treatment pose a concern.